Beneficial microbes in agro-ecology. - Amaresan, N.; Kumar, M. Senthil; Annapurna, K. (Kannepalli); Kumar, Krishna; Sankaranarayanan, A. (Academic Press, 2020)
Beneficial Microbes in Agro-Ecology: Bacteria and Fungi is a complete resource on the agriculturally important beneficial microflora used in agricultural production technologies. Included are 30 different bacterial genera relevant in the sustainability, mechanisms, and beneficial natural processes that enhance soil fertility and plant growth. The second part of the book discusses 23 fungal genera used in agriculture for the management of plant diseases and plant growth promotion. Covering a wide range of bacteria and fungi on biocontrol and plant growth promoting properties, the book will help researchers, academics and advanced students in agro-ecology, plant microbiology, pathology, entomology, and nematology. --